The Ukrainian Emotionally-Evaluative Phraseologisms in the Political Discourse (Linguostylistic Studies, 2019)
Dominance of the cognitive-discursive paradigm in the linguistic studies allows  answering a number of important scientific issues, such as identifying verbal and rhetorical strategies in the political discourse, revealing methods and regularities of verbalization of complex cognitive, psychological, mental, cultural, and historic categories. Modern approaches in linguistics facilitate the comprehensive study of function features of both traditional and transformed phraseological units in the political discourse. The new approaches rely on the latest findings in the adjacent branches of linguistics, like psycholinguistics, cognitive linguistics, pragmalinguistics. The abovementioned determines the relevance of the research.The study seeks to identify and analyze the communicative, pragmatic, structural, and semantic characteristics of phraseologism functioning as a means of expressing emotionally evaluative statements in the political discourse.The in-depth analysis of the linguistic facts, particularly the use of phraseological units with evaluative meaning, allows revealing the stereotypical models of the Ukrainian political reality perception. Political realities are often characterized by the use of phraseologisms expressing positive or negative attitude to the depicted event. The emotional-evaluative characteristics of phraseologisms in the political discourse provide a basis for effective communication, realizing a wide range of communicative functions: message, expression, influence, even the manipulation of human consciousness.Phraseologisms reflect the evaluative features both implicitly and explicitly, which is impossible without the contextual environment in which the phraseologism functions. Political discourse is dominated by phraseologisms, the meaning of which reflects a disapproving evaluation, because they characterize situations where one gets rich or profane in some dishonest way, when one causes material damage, which leads to poverty of the population.
Keywords: phraseological unit (PhU); evaluative meaning; political discourse; structural and semantic transformation